Integration of Technology and Resource Management in the Modern Education System - Besse Maryani; Sulis Anggraeni; Maulana Akbari; Aslamiah; Ahmad Suriansyah (Jurnal Pendidikan (Teori dan Praktik), 2026)
Despite the growing discourse on digital transformation in education, there is a scarcity of empirical research specifically examining the synergy between technology integration and resource management within Indonesian public senior high schools. Addressing this gap, this study aims to explore the integration of technology and resource management at SMAN 1 Panyipatan, focusing on the utilization of Management Information Systems (MIS), Learning Management Systems (LMS), and human resource management strategies. Using a qualitative case study approach, the research involved teachers, administrative staff, and the school principal as informants through semi-structured interviews, participatory observation, and document analysis. The findings indicate that while technology integration has improved administrative efficiency, data transparency, and student engagement, challenges such as uneven digital literacy, limited infrastructure, and the need for ongoing technical support remain. Ultimately, the study demonstrates that technology implementation, underpinned by effective resource management, significantly strengthens teacher professionalism and school operational effectiveness. These insights provide critical implications for school management policy and digital transformation strategies in similar educational contexts.